Acquiring and maintaining competency in gastrointestinal endoscopy. Issue 3 (June 2016) - Dubé, Catherine; Rostom, Alaa
Abstract: In recent years, an important transformation has taken place in the field of gastrointestinal endoscopy training. Two important movements have helped initiate this transformation: patient centered quality and competency based training. Patient centered quality in endoscopy became an important focus for colorectal cancer screening programs, as it was acknowledged that colonoscopy services played a central role in the outcomes of screening. This prompted the need to close the quality loop through the development of innovative endoscopist training and upskilling programs. As well, the importance of leadership skills and leadership training was highlighted as a key factor in effective quality improvement. Competency-based training depends on well-defined goals of training and on the regular documentation and review of the learner's progress. This is facilitated by objective assessment and performance enhancing feedback, enabled by measurement tools that can provide a quantitative or qualitative assessment and identify areas in need of further development. Simulators and scope imagers can aid the acquisition of technical skills, particularly in the novice phase. These important advances in our evolving concepts around endoscopy training have also raised many questions, highlighting important knowledge gaps which, we hope, will be addressed in coming years.